1998
DOI: 10.1006/abio.1997.2544
|View full text |Cite
|
Sign up to set email alerts
|

Purification of the Alkaloid Lycorine and Simultaneous Analysis of Ascorbic Acid and Lycorine by Micellar Electrokinetic Capillary Chromatography

Abstract: The pyrrolophenanthridine alkaloid lycorine has frequently been used as a specific inhibitor to help elucidate the function of ascorbic acid (vitamin C) in a wide range of biological processes. It was recently reported that this function can be exercised by inhibiting the activity of L-galactono-1,4-lactone dehydrogenase, the terminal enzyme of ascorbic acid biosynthesis, although working with the purified enzyme, we have been unable to repeat this result. Here, we present a procedure for the purification and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Nonetheless, the possibility that lycorine exerts its effects via mitochondrial mechanisms is supported by studies in Saccharomyces cerevisiae, which have demonstrated that cells lacking mitochondrial DNA are resistant to lycorine. 50 Elderly CLL patients are commonly excluded from clinical trials because of their susceptibility to the development of cytopenia and infections and in younger patients there is an inevitable development of chemoresistance to conventional agents. Thus more targeted therapies are urgently required.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the possibility that lycorine exerts its effects via mitochondrial mechanisms is supported by studies in Saccharomyces cerevisiae, which have demonstrated that cells lacking mitochondrial DNA are resistant to lycorine. 50 Elderly CLL patients are commonly excluded from clinical trials because of their susceptibility to the development of cytopenia and infections and in younger patients there is an inevitable development of chemoresistance to conventional agents. Thus more targeted therapies are urgently required.…”
Section: Discussionmentioning
confidence: 99%
“…In plants, it also inhibits cyanide-insensitive respiration, peroxidase activity, and protein synthesis (451)(452)(453). Thus, differing sensitivity to the alkaloid among cells devoid of mitochondrial DNA (rho 0 ) and cells with mitochondrial DNA either rho + or rho � has been found in yeasts (440,448,454,455), rho 0 cells being resistant to high concentrations of the drug (450,(456)(457)(458). Thus, differing sensitivity to the alkaloid among cells devoid of mitochondrial DNA (rho 0 ) and cells with mitochondrial DNA either rho + or rho � has been found in yeasts (440,448,454,455), rho 0 cells being resistant to high concentrations of the drug (450,(456)(457)(458).…”
Section: Lycorine Typementioning
confidence: 99%
“…Lycorine has been isolated from a variety of plants (see references in Del Giudice et al 1984;Lin et al 1995;Kushida et al 1997;Campbell et al 1998;Davey et al 1998), and shown to possess an inhibitory effect on tumor cell apoptosis (Yui et al 1998), K-ras-transformed fibroblasts (Kushida et al 1997), and multi-drug-resistant phenotype cells (Hua et al 1997). An antimalarial property has also been reported for lycorine (Campbell et al 1998).…”
Section: Discussionmentioning
confidence: 98%
“…In previous papers we have demonstrated that the alkaloid lycorine (Davey et al 1998) is able to differentiate between cells devoid of mitochondrial DNA (rho 0 ) and cells with mitochondrial DNA, either rho + or rho -. Wild-type rho + cells, neutral rho -cells, and moderately suppressive rho -cells are all sensitive to the lycorine; rho 0 cells, however, are resistant to high concentration of the drug (Del Giudice et al 1984).…”
Section: Introductionmentioning
confidence: 99%